Numerical simulation of electroosmosis regulated peristaltic transport of Bingham nanofluid. (October 2019) - Tanveer, Anum; Khan, Mair; Salahuddin, T.; Malik, M.Y.
Highlights: Nanoparticle phenomena has been highlighted. Electroosmotic flow is considered of Bingham fluid. Mathematical peristaltic flow on Bingham Nanofluid. Walls are assumed to be flexible. Exact and analytical solutions are presented. Abstract: The effects of slip condition and Joule heating on the peristaltic flow of Bingham nanofluid are investigated. The flow is taken in a porous channel with elastic walls. Mathematical formulation is presented under the assumption of long wavelength and small Reynolds number. The transformed equations for the flow are solved to seek values for the nanoparticles velocity, concentration and temperature along the channel length. Graphs are plotted to evaluate the behavior of various physical parameters on flow quantities in both slip and no-slip cases. The main features of the physical parameters are highlighted on the inclined non uniform channel. The results show an increment in velocity with rise in inclination and porosity while it reduces with magnetic field. Moreover, nanofluid favors the heat transfer and decline the concentration.